Social anxiety in young people with first‐episode psychosis: Pilot study of the EMBRACE moderated online social intervention. Issue 1 (30th December 2019) - McEnery, Carla; Lim, Michelle H.; Knowles, Ann; Rice, Simon; Gleeson, John; Howell, Simmone; Russon, Penni; Miles, Chris; D'Alfonso, Simon; Alvarez‐Jimenez, Mario
Abstract: Aim: We conducted a single‐group pilot study to evaluate the feasibility, acceptability and safety of a novel online intervention (entitled EMBRACE) that includes expert and peer moderation, therapeutic comics and social networking features. The cognitive‐behavioural‐based intervention was specifically designed to treat social anxiety as a primary treatment target in youth with first‐episode psychosis (FEP). Methods: The 10 participants (17‐26 years; M age = 23 years) had a diagnosis of FEP and experienced significant levels of social anxiety as defined by exceeding a sub‐threshold clinical score (>30) on the Social Interaction Anxiety Scale (SIAS). They had access to the EMBRACE intervention for 2 months. Results: In total, seven out of ten participants completed eight modules or more (total of 12 modules). All participants rated the intervention as positive and safe, and endorsed recommending it to others who experience social anxiety. Improvement in pre‐post social anxiety symptoms, as measured via the SIAS ( d = −1.70, P = .0005) and the Liebowitz Social Anxiety Scale ( d = −1.35, P = .002) were found. No statistically significant pre‐post improvements were found for depressive or loneliness symptoms. Conclusion: EMBRACE was shown to be a feasible, acceptable, and safe online intervention to specifically target social anxiety as a primary treatment concern in young people with FEP.